2019
DOI: 10.1108/ijmpb-03-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Critical Chain Project Management literature

Abstract: Purpose The purpose of this paper is to analyze the state of the art in Critical Chain Project Management (CCPM), outlining the CCPM literature to date, in an effort to guide future studies. Design/methodology/approach The paper is based on a bibliometric analysis using Scopus and Web of Science databases. The authors identified the principal journals, articles and authors regarding the research theme, as well as the authors elaborated co-citation and co-occurrence network maps to support the analysis. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
11
0
2
Order By: Relevance
“…Throughout this period, we witnessed the evolution of the method. In this sense, the contribution of this article is that it responds to the additional research suggestions of other authors on the subject, which exposes the evolution of the method over time, identifying further research areas [9,20]. The present inquiry deals with some of these issues, such as application to the development of new products, the additional techniques applied ("full kitting" and Kanban), or aspects related to the empirical testing of the method improvements.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Throughout this period, we witnessed the evolution of the method. In this sense, the contribution of this article is that it responds to the additional research suggestions of other authors on the subject, which exposes the evolution of the method over time, identifying further research areas [9,20]. The present inquiry deals with some of these issues, such as application to the development of new products, the additional techniques applied ("full kitting" and Kanban), or aspects related to the empirical testing of the method improvements.…”
Section: Introductionmentioning
confidence: 95%
“…As in DBR, workflow improvement is promoted to achieve this purpose. Thus, time management is the central aspect of this approach, based on the belief that it will have a positive impact on scope and budget management [20].…”
Section: The Theory Of Constraints (Tocs) and Ccpmmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the domains concerning supply chain and critical chain concepts in Engineer, Procurement and Construct (EPC) projects were integrated [133]. Furthermore, overarching studies concerning CCPM were also conducted [134,135] and it was concluded that CCPM offers a number of opportunities for further research on scheduling topic. Since schedule is one of the vital requirements for the delay analyses, CCPM is also to be considered for delay analysis domain by researchers as an innovative method of planning and project management.…”
Section: Contributions Of Critical Chain Project Managementmentioning
confidence: 99%